SURVEI TINGKAT KEPUASAN MAHASISWA TERHADAP PENGGUNAAN APLIKASI BELAJAR SELAMA PERKULIAHAN DARING - Veramyta Maria Martha Flora Babang; Maria Andriani Barek Ladjar; Katharina Edeltrudis Perada Korohama (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2020)
The purpose of this study is to determine the level of student satisfaction with the use of learning applications during the online lecture period. The learning applications used are E-Learning, Edmodo, and Zoom. These three learning applications are given during the even semester of the 2019/2020 academic year to students of the Penjaskesrek and Guidance and Counseling study program in courses that are managed by the research team. This research is an experimental study using a 3x3 factorial design and data collection techniques using a questionnaire filled out via google form. The level of satisfaction is divided into three indicators, namely usability dimensions, information quality dimensions and service interaction dimensions. The results showed that there are differences in each learning application on the indicators of satisfaction. In the Usability Dimension, Edmodo application has the highest Mean Ranking of 36.86, and in the Information quality dimension the E-learning application has the highest Mean Ranking of 38.72, while the service interaction dimension of the E-learning application has the highest Mean Ranking of 36.92. So it can be concluded from these three learning applications that E-learning applications have the most significant influence on student satisfaction